USM TRANSFERS KNOWLEDGE TO 43 ‘ORANG ASLI’ FAMILIES AT KAMPUNG LANGKOR - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SUNGAI SIPUT, 1 February 2016 – The ‘orang asli’ population in Kampung Langkor, a village in northern Sungai Siput, Perak could not hide their feelings of gratitude and was thankful when receiving a visit by a delegation from Universiti Sains Malaysia (USM) recently.